2018
DOI: 10.1038/s41598-018-19330-0
|View full text |Cite
|
Sign up to set email alerts
|

Diesel engine performance and emissions with fuels derived from waste tyres

Abstract: The disposal of waste rubber and scrap tyres is a significant issue globally; disposal into stockpiles and landfill poses a serious threat to the environment, in addition to creating ecological problems. Fuel production from tyre waste could form part of the solution to this global issue. Therefore, this paper studies the potential of fuels derived from waste tyres as alternatives to diesel. Production methods and the influence of reactor operating parameters (such as reactor temperature and catalyst type) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 70 publications
0
28
0
1
Order By: Relevance
“…At low engine speeds, CO is converted to the CO2. Oxidized carbons caused to release higher amount of CO2 [23].…”
Section: Results and Dıscussıonmentioning
confidence: 99%
“…At low engine speeds, CO is converted to the CO2. Oxidized carbons caused to release higher amount of CO2 [23].…”
Section: Results and Dıscussıonmentioning
confidence: 99%
“…Step 2 [1] to vary the CR, so that CR can be changed during running condition. The setup has panel box consisting of air box fitted with manometer, a fuel tank, fuel measuring unit, transmitters for air and fuel flow measurements, indicator and hardware interface.…”
Section: Methodsmentioning
confidence: 99%
“…Tires after use are environmentally hazardous as these do not readily biodegrade and recover from their constituent components [1]. Around 1500 million tires are generated every year which potentially goes wasted and can be recycled to utilize [2].…”
Section: Waste Tyre-a Potential Fuelmentioning
confidence: 99%
“…This is due to the fact that TPO has higher aromatic content, and hence may result in incomplete combustion and more HC emission for B15 and B20 compared to the other test fuels used in this study. The HC values for diesel, JME, B10, B20, B30 and B40 are 23,18,19,21,25 and 31 ppm are at full load.…”
Section: Fig3 Variation Of the Unburnt Hydrocarbon Emission With Bramentioning
confidence: 99%
“…Also, they observed that 25% of neat Castor oil blended with 75% of diesel is the well-suited blend for Diesel engine without heating and/or without implementing any engine modifications. Deepanraj et al, [19] studied the performance characteristics of a single cylinder direct injection diesel engine with palm oil biodiesel and its blends. From their results, they reported that the acceptable\ thermal efficiencies were obtained, and the specific fuel consumption and exhaust gas temperatures were higher than the results obtained with diesel fuel.…”
Section: Introductionmentioning
confidence: 99%